Whither local governance in contemporary China? Reconfiguration for more effective policy implementation. Issue 1 (2nd January 2016) - Ahlers, Anna L.; Heberer, Thomas; Schubert, Gunter
Abstract: This article describes China's reorganization of its local governance system since the early 2000s. Policy shifts, administrative restructuring and intensified public inclusion have considerably modified local governance, especially in the country's vast rural areas and, we argue, have laid the groundwork for continuous and more effective policy implementation amidst increasing complexity and challenges. Based on years of fieldwork on new rural development policies, urbanization programs and private sector development in China, we start by briefly describing the most important developments in local governance, especially at the county level and below. We then concentrate on two aspects with particular relevance: first, we trace the reconfigured characteristics of internal governmental procedures of policy adjustment and implementation. Second, we find new types of external stakeholder inclusion, which we analyze based on the example of local government interactions with private entrepreneurs in promoting development blueprints and strengthening public goods provision. In conclusion, we contend that current Chinese local governance is a dynamic and delicate combination of expanding local administrative autonomy, external actor inclusion and the Party State's re-emergent aim of pervasive steering. At a minimum, the resulting governance arrangements appear able to generally strengthen the political regime's implementation capacities.